Respuesta :
Answer:
[tex]g(x) = -0.1x^2 + 0.5x + 3.6[/tex]
Step-by-step explanation:
Given
[tex]h(x) = -0.1x^2 + 0.7x + 3[/tex]
Required
Determine the new function
From the question, we understand that the new function wants the water to hit the ground 1 ft farther.
1 ft farther implies x + 1
So, in the given function, we substitute x + 1 for x in [tex]h(x) = -0.1x^2 + 0.7x + 3[/tex]
This gives:
[tex]h(x + 1) = -0.1(x + 1)^2 + 0.7(x + 1) + 3[/tex]
Expand Bracket
[tex]h(x + 1) = -0.1(x + 1)(x + 1) + 0.7(x + 1) + 3[/tex]
[tex]h(x + 1) = -0.1(x^2+2x+1) + 0.7(x + 1) + 3[/tex]
[tex]h(x + 1) = -0.1x^2-0.2x-0.1 + 0.7x + 0.7 + 3[/tex]
Collect Like Terms
[tex]h(x + 1) = -0.1x^2-0.2x + 0.7x + 0.7 + 3-0.1[/tex]
[tex]h(x + 1) = -0.1x^2 + 0.5x + 3.6[/tex]
Hence, the new function is:
[tex]g(x) = h(x + 1) = -0.1x^2 + 0.5x + 3.6[/tex]
[tex]g(x) = -0.1x^2 + 0.5x + 3.6[/tex]
The new model for path of water will be, [tex]h(x+1)=-0.1x^{2} +0.5x+3.6[/tex]
To understand more, check below explanation.
Height function:
The height h (in feet) of water spraying from the garden house can be modeled by,
[tex]h(x)=-0.1x^{2} +0.7x+3[/tex]
where x is the horizontal distance (in feet) from where you are standing.
Since, you raise the hose so that the water hits the ground 1 foot farther from where you are standing.
So that, new function will be,
[tex]h(x+1)=-0.1(x+1)^{2} +0.7(x+1)+3\\\\h(x+1)=-0.1(x^{2} +2x+1)+0.7x+0.7+3\\\\h(x+1)=-0.1x^{2} -0.2x-0.1+0.7x+0.7+3\\\\h(x+1)=-0.1x^{2} +0.5x+3.6[/tex]
Learn more about the function here:
https://brainly.com/question/25638609